PENGARUH GAYA BELAJAR VISUAL, AUDITORI, KINESTETIK TERHADAP PENCAPAIAN IPAS KELAS IVB SDN 64/1 MUARA BULIAN - Chinta Dwi Zahwa; Rana Nazihah; Mutiara Rahmadani; Revara Gracia Venesa; Khairunnisa (STKIP Subang, 2026)
The implementation of IPAS (Science and Social Studies) learning in elementary schools often encounters obstacles due to students’ diverse learning styles. A mismatch between teaching methods and students’ characteristics can reduce learning effectiveness. This study aims to identify the dominant learning style among fourth-grade students at SDN 64/1 Muara Bulian and its implications for IPAS learning. A descriptive quantitative approach was employed by distributing a learning style questionnaire to 25 students. The instrument consisted of three main categories: visual, kinesthetic, and auditory. The results showed that the visual learning style was dominant, with 44% (11 students), followed by kinesthetic at 36% (9 students), and auditory at 20% (5 students). This finding indicates that most students comprehend material more easily through visual media such as images, concept maps, and instructional videos. The results emphasize the importance of teachers designing adaptive and varied IPAS learning strategies by combining visual, kinesthetic, and auditory approaches to accommodate all students effectively.